Investigating the potential of fish muscle-based gels as functional feed supplements for eco-friendly aquaculture - Jham Lal; Pradyut Biswas; Soibam Khogen Singh; Reshmi Debbarma; Anand Vaishnav; Gusheinzed Waikhom; N. Sureshchandra Singh; Dharmendra Kumar Meena (Aquaculture Reports)
The study investigated the efficiency of a novel gel-based diet in promoting the growth, feed acceptance, and physiological function of an endemic ornamental fish, Pethia conchonius. The study comprised two experiments, firstly, optimisation of gel parameters (pH and temperature) and secondly, the effect of the formulated feed on growth, acceptability, and physiology of the fish. In the first experiment, gels were formulated at different pH levels (5 and 7) and temperatures (50°C, 70°C, and 90°C). A control group was included to maintain the pH of fish muscle tissue. Gels formulated at pH 7 and 70°C demonstrated enhanced functional qualities (gel strength, texture, colour, stability, and nutrient retention) and received positive acceptance by the fish. Texture, adhesiveness, and cohesiveness was enhanced with elevated pH and temperature. In the second experiment, fish (average initial weight: 3.62 ± 0.57 g) were given the prepared gels in 45 L glass aquaria for 30 days. The maximum feed acceptance (14.73 ± 0.20) was recorded in the 5pH-70°C treatment group, whereas the minimum (10.73 ± 0.15) was noted in a 5pH-70°C group. Gel-based diets enhanced haematological and digestive functions compared to the control group. Water quality parameters were optimum in experimental groups, indicating improved nutrient retention. This work introduces an innovative and sustainable method for formulating a gel-based feed for ornamental fish.